Determinan Keputusan Pembelian Netflix: Perspektif Citra Merek, Persepsi Harga dan Kualitas Produk - Indira, Christera Kuswahyu; Dirnaeni, Desti; Ardiansyah, Irfan; Ardiyansyah, Dimas (INVESTASI : Inovasi Jurnal Ekonomi dan Akuntansi, 2025)
The aim of this research is to analyze the influence of brand image, price perception and product quality on purchasing decisions and to find out which variables are most dominant in purchasing decisions. The data used in this research used a questionnaire instrument and valid data was collected from 120 respondents. The sampling method in this research is nonprobability sampling with the Accidental Sampling technique. The testing tool used is SPSS. The results show that the variables brand image, price perception, product quality and promotion simultaneously influence purchasing decisions. The brand image variable partially influence purchasing decisions, while the price perception and product quality variables have no influence on purchasing decisions and the most dominant variable in purchasing decisions is the brand image variable.